SISTEM PENDUKUNG KEPUTUSAN PENGAKTIFAN FITUR 4G LTE PADA BTS MENGGUNAKAN METODE PROMETHEE BERBASIS WEB - Yogi Sutrisna, I Komang; Sudarma, Made; Arya Mertasana, Putu (Jurnal SPEKTRUM, 2017)
Rapid development in information technology and telecommunications has encouraged the development of information. One of them is information about the intense competition in the development of alternative access networks. 4G network is intended as a solution for communications network which considered comprehensive and secure, with data speeds much faster than the previous generation. In general it is asked to provide high quality service and faster data transfer speeds. Planning a system which can assist in the selection of BTS for indispensable 4G feature is enable telecommunications network operators in determining which BTS that is suitable for the desired criteria. This research can be made a DSS (Decision Support System) web-based to solve the problem of the selection of alternatives BTS. Development of the applications built using Waterfall methodology System. While for method of decision-making is used Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). In the implementation stages, the system uses the PHP programming language and MySQL as the database. Decision support systems can produce alternatives BTS that suggested according to criteria based on the results of analysis methods PROMETHEE. Differences of two types of manual calculation and use the system shown at the three best ranked of 20 base stations were selected.